Perkembangan awal systema nervosum centrale embryo gallus setelah pemberian insektisida furadan 3G=Early Development of the Central Nervous System of the Chick - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1988)
In the effort to obtain the profile of teratogenic effects of the insecticide Furadan 3G on the central nervosum system of the embryo, the influence of insecticide Furadan 3G on the early development of the central nervosum system of the chick embryo was investigated by injecting Furadan 3G into the yolk sac on the first day incubated egg. Three different concentrations of a single dose of Furadan 3G, i.e, 11 mg, 5.5 mg and 2.75 mg/egg were used and the early development of the central nervous system was observed stereomicroscopically by observing the closing of the brain primary vesicles, the 5-vesicle stage of the brain development and the formation of the flexures. The results of the experiment showed that the treatment of three different doses of Furadan 3G caused inhibition of the closure of the neural tube and the formation of the 5-vesicles of the brain of the chick embryo.